الجهاد في ضوء القرآن السنة - Nur Habibah Bt Abdul Wahab (Universiti Sains Islam Malaysia, 2010)
The purpose of the research made is to give clear picture about actual means of jihad from the perspective of al-Quran and Sunnah .The act of jihad is very important in Islam because the Muslims are encouraged to jihad according to Islamic ways. It's to defend Islamic religion to avoid from enemy. In this research apparent about the world of jihad in literature and the term. Also, it's clearly about jihad items like jihad to defend our self, properties, and anything else. Besides that, this research also describe about the rules of jihad and to clear about wajib, mandub, mubah, makruh or haram. Also, the jihad got from the proof of al-Quran and Sunnah and ulama' views. Nevertheless, this research is based on the information and the data, which got from the sources and references that was guideline in academic methods, which include the process of studying, describing and deeply studying on current issues and situation.